Optimality conditions in convex optomization : a finite-dimensional view - Dhara, Anulekha; Dutta, Joydeep (Boca Raton : CRC Press, 2012)
Covering the current state of the art, this book explores an important and central issue in convex optimization : optimality conditions. It focuses on finite dimensions to allow for much deeper results and a better understanding of the structures involved in a convex optimization problem.
Includes bibliographical references (p. 413-421) and index.
Keywords: Mathematical optimization